Prolonged blood pressure reduction by orally active renin inhibitor RO 42-5892 in essential hypertension. Issue 6745 (28th July 1990) - van den Meiracker, A H; Admiraal, P J; Man in 't Veld, A J; Derkx, F H; Ritsema van Eck, H J; Mulder, P; van Brummelen, P; Schalekamp, M A
Abstract : OBJECTIVE--To investigate the effects of a novel specific renin inhibitor, RO 42-5892, with high affinity for human renin (Ki = 0.5 x 10(-9) mol/l), on plasma renin activity and angiotensin II concentration and on 24 hour ambulatory blood pressure in essential hypertension. DESIGN--Exploratory study in which active treatment was preceded by placebo. SETTING--Inpatient unit of teaching hospital. PATIENTS--Nine men with uncomplicated essential hypertension who had a normal sodium intake. INTERVENTIONS--Two single intravenous doses of RO 42-5892 (100 and 1, 000 micrograms/kg in 10 minutes) given to six patients and one single oral dose (600 mg) given to the three others as well as to three of the patients who also received the two intravenous doses. RESULTS--With both intravenous and oral doses renin activity fell in 10 minutes to undetectably low values, while angiotensin II concentration fell overall by 80-90% with intravenous dosing and by 30-40% after the oral dose. Angiotensin II concentration was back to baseline four hours after the low and six hours after the high intravenous dose and remained low for at least eight hours after the oral dose. Blood pressure fell rapidly both after low and high intravenous doses and after the oral dose and remained low for hours. With the high intravenous dose the daytime (0900-2230), night time (2300-0600), and next morning (0630-0830) systolic blood pressures were significantly (p less than 0.05) lowered by 12.5 (95% confidence interval 5.6 to 19.7), 12.2 (5.4 to 19.3), and 10.7 (3.2 to 18.5) mm Hg respectively, and daytime diastolic pressure was lowered by 9.3 (2.2 to 16.8) mmHg. With the oral dose daytime, night time, and next morning systolic blood pressures were lowered by 10.3 (5.5 to 15.4), 10.5 (4.2 to 17.2), and 9.7 (4.0 to 15.6) mm Hg, and daytime and night time diastolic pressures were lowered by 5.8 (0.9 to 11.0) and 6.0 (0.3-12) mm Hg respectively. CONCLUSIONS--The effect of the inhibitor on blood pressure was maintained over a longer period than its effect on angiotensin II. RO 42-5892 is orally active and has a prolonged antihypertensive effect in patients who did not have sodium depletion. This prolonged effect seems to be independent, at least in part, of the suppression of circulating angiotensin II.